Between turkic and slavic. Materials for the investigation of slavic loanwords in the earliest west Karaim sources - Németh, Michał (Vilnius University Proceedings, 2024)
This paper offers an overview of the oldest West Karaim written sources with a special focus on the Slavic lexical elements they contain. The main goal of the article is to present the phonetic adaptation processes these loanwords underwent and to answer the question from which Slavic languages they were borrowed. The Slavic linguistic material presented in this article was collected from manuscripts created in the first 100 years of the written history of West Karaim, i.e. in the period between 1671 and 1772. The year 1772, i.e. the year in which the First Partition of Poland took place, has been chosen as the closing time limit mainly because the second half of the 18th century was the time when Slavic–West Karaim bilingualism became a widespread phenomenon which, in turn, resulted in markedly different adaptation processes than in the early decades of these contacts.